THE IMPACT OF TELEMEDICINE ON PREOPERATIVE AND POSTOPERATIVE CARE IN SURGERY - Abdulaziz Nafea Alrashdi, Maged Hamed Al Harbi, Abdulaziz Saleh Saud Sharbah, Ibrahim Khalil Almubarrazi, Mahdi Mojaly Alamri, Abdulaziz Abdullah Alkahtani, Mohammad Abdullah Alghamdi, ,; Meshari Abdullah Saleh Alharbi, Hamoud Ahmad Mousa Abutaweel, Abdulaziz Saleh Saud Sharbah, Ramy Mahmmod Eid, Mohammed Saad Almutairi, Hussam Jamaan Alzahrani, (Chelonian Research Foundation, 2022)
Telemedicine refers to a healthcare service in which doctors interact with patients from a distance utilizing telecommunication technology. Telemedicine is utilized for pre- and after surgical assistance, surveillance, and surgical education. The objective of our study was to examine the diverse array of telemedicine tools used in the field of surgical care. A comprehensive search was conducted in MEDLINE, EMBASE, CINAHL, and Science Direct databases to identify relevant material published from the beginning of these databases. No limitations were placed on the language of the articles. The search phrases used were: mobile phones, telemedicine, internet access, video, online, teleconferencing, distant advice, surgery, preoperative, perioperative, postoperative, and surgical operations. Included studies focused on the use of telemedicine during the pre-, peri-, or post-surgery stages, and included a comparison between standard surgical care and surgical telemedicine. Patients have reported several advantages of adopting telemedicine, including the ability to prevent needless visits to hospitals, saving time, and lowering the number of lost working days. Telemedicine in surgical treatment offers advantages to both patients and professionals. Keywords: Telemedicine, surgical process, satisfaction, monitoring